Tanggung Jawab Hukum PT. Gojek Indonesia terhadap Ketidaksesuaian Identitas Driver dalam Layanan Go-Send di Kota Serang Berdasarkan Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen - Dewi, Rachawanti Puspita; Agus, Dede; Mucharom, Rully Syahrul (Journal of Contemporary Law Studies, 2025)
This study aims to analyze the legal responsibility of PT. Gojek Indonesia regarding the mismatch of driver identity in the Go-Send delivery service in Serang City, based on Law Number 8 of 1999 concerning Consumer Protection. The main issue examined is the loss or non-delivery of goods due to drivers whose identities do not match the information displayed in the application. The research employs an empirical juridical approach, collecting primary data through interviews and secondary data through literature studies. The findings reveal that PT. Gojek holds legal liability to compensate consumers for their losses, either in the form of money or equivalent goods, as stipulated under consumer protection regulations. However, in practice, the dispute resolution process has not been effective, as consumers have not yet received clear compensation. Consequently, some consumers have escalated the matter to consumer protection agencies. The study concludes that PT. Gojek must improve identity verification procedures for its drivers and enhance the dissemination of information regarding claim mechanisms to users. Additionally, it is recommended to implement a mandatory-read agreement feature to ensure that consumers understand their rights. These efforts are expected to strengthen consumer trust and the overall credibility of Go-Send services.